Ultra-thin electrospun nanofibers for development of damage-tolerant composite laminates - An, Donglan; Lotfian, Saeid; Mesbah, Daria; Ayre, David; Yoosefinejad, Ata; Thakur, Vijay Kumar; Yazdani Nezhad, Hamed (Elsevier, 2019)
The present article overcomes existing challenges in inter-laminar toughening of novel multifunctional fiber-reinforced polymer composites via development and embedment of highly stretched, ultra-thin electrospun thermoplastic nanofibers made of polyamide 6.6. The nanofibers exhibit significant enhancement of the composite laminate's structural integrity with almost zero weight penalty via ensuring a smooth stress transfer throughout the plies and serving tailoring mechanical properties in desired directions, with no interference with geometric features, e.g., thickness. The findings for 1.5 g per square meter electrospun nanofibers have demonstrated, on test coupon specimens, improvements up to 85% and 43% in peak load and crack opening displacement, respectively, with significant improvement (>25%) and no sacrifice of fracture toughness at both initiation and propagation phases. The initial stiffness for the modified specimens was improved by nearly 150%. The enhancement is mainly due to nanofibers contributing to the stiffness of the resin-rich area at the crack tip adjacent to the polytetrafluoroethylene (PTFE) film. Glass fiber-reinforced woven phenolic pre-impregnated composite plies have been modified with the nanofibers (each layer having an average thickness of <1 micron) at 0.5, 1.0, 1.5, 2.0 and 4.0 gsm, electrospun at room temperature on each ply, and manufactured via an autoclave vacuum bagging process. Inter-laminar fracture toughness specimens were manufactured for Mode I (double cantilever beam) fracture tests. It was found that there is threshold for electrospun nanofibers density, at which an optimum performance is reached in modified composite laminates. The threshold is influenced by the plastic deformation mechanism at the crack tip, the fiber bridging between the adjacent plies afforded by the nanofibers, and the density of the electrospun fibers. Such optimum performance was found linked to the nanofibers at a specific density. Excessively increasing above the threshold (herein >2.0 gsm) degrades the adhesion properties (chemical bonding) between glass fibers and the phenolic matrix. The density of nanofibers increases, so does the likelihood of forming a physical barrier between the plies resulting in the loss of resin flow and poor adhesion. Such an effect was evident from microscopic investigations and reduction in fracture toughness data at the initiation and propagation phases.
Keywords: Electrospinning; Nanofibers; Polymer matrix composite; Fracture toughness; Chemical bonding; Nanofiber deformation